Exploring the association between breastfeeding and the risk of developing autism spectrum disorders - Rehana Yasmeen,; Farah Mehboob,; Sarah Razaq,; F.A. Rathore, (Journal of the Pakistan Medical Association, 2026)
Autism spectrum disorder (ASD) is a complex neurodevelopmental condition with rising prevalence globally, including Pakistan. While genetic factors substantially contribute to ASD risk, environmental and early-life nutritional factors are also being investigated. One such factor is infant feeding practices specifically breastfeeding, its duration and exclusivity. Human breast milk provides comprehensive protection via providing essential nutrients with immune defence and neurobiological regulation supporting optimal brain development. Despite these benefits, breastfeeding rates in Pakistan remain low. This mini-review explores the existing literature on the potential link between breastfeeding and ASD with a focus on epidemiological evidence and underlying biological mechanisms. While some studies suggest that breastfeeding may reduce the risk of ASD, the evidence is inconclusive due to methodological differences, recall bias, and cultural factors. Data from low- and middle-income countries is lacking and call for an urgent need for robust longitudinal research in Pakistan to better study this association and guide costeffective public health strategies. Keywords: Autism, Childhood disability, Pakistan, breastfeeding practices, developmental delay, developing countries, LMIC